How Myanmar Female Workers Negotiate In Their Workplace At Chiang Rai, Thailand - Yi, Tin Moe (Advances in Social Sciences Research Journal, 2019)
In Thailand, there are many migrants from Myanmar who distributed in five top sectors which are agriculture, construction, fishery related, agriculture related and service. The total number of Myanmar migrant workers in Thailand today is estimated to be about between 1,500,000 and 1,600,000 with over 100,000 women from Myanmar employed as domestic workers. In Myanmar, in the political affairs, women are effectively excluded from participating in the negotiations for peace. In this article, the researcher explored how woman workers negotiate at their workplace. The present study was based on the case study of Myanmar female workers’ attitudes towards whether and how they negotiated in their workplace. To assess their attitude, three categories focused by Weaver (2011) were applied to get the information. It is observed that most of the female workers had the same attitude that they did not ask any more to their employer and did not want to negotiate because some were satisfied with their jobs as their head solved their problems on behalf of them and some were lack of confidence. The women are weak, emotional and submissive so they might not be successful negotiators.